High-pressure crystal structures of TaAs from first-principles calculations. (August 2016) - Lu, Mingchun; Guo, Yanan; Zhang, Miao; Liu, Hanyu; Tse, John S.
Abstract: In this work, we systematically studied the phase transition of TaAs under high pressures and reported three high-pressure structures P -6 m 2 (hexagonal, stable at 13–32 GPa), P 21 / c (monoclinic, stable at 32–103 GPa) and Pm- 3 m (cubic, stable above 103 GPa), by using particle swarm optimization in combination with first principles electronic structure methodology. All predicted structures are dynamically stable, since there is no imaginary mode to be found in the whole Brillouin zone. At high pressures, the TaAs was found to become superconductor with the superconducting critical temperature of 1 K at about 100 GPa. Highlights: This paper systematically studied the high-pressure crystal structures of TaAs in theory. We have studied the electronic structure and superconductor of TaAs. Our calculation results reveal that the TaAs was found to become superconductor with the superconducting critical temperature of 1 K at about 100 GPa.